LncRNA-T199678 Mitigates α-Synuclein-Induced Dopaminergic Neuron Injury via miR-101-3p - Bu, Lu-Lu; Xie, Ying-Yu; Lin, Dan-Yu; Chen, Ying; Jing, Xiu-Na; Liang, Yan-Ran; Peng, Su-Dan; Huang, Kai-Xun; Tao, En-Xiang (Frontiers in Aging Neuroscience, 2020)
Parkinson's disease (PD) is the second most common neurodegenerative disorder characterized by dopaminergic neuron death and the abnormal accumulation and aggregation of α-Synuclein (α-Syn) in the substantia nigra (SN). Although the abnormal accumulation of α-Syn can solely promote and accelerate the progress of PD, the underlying molecular mechanisms remain unknown. Mounting evidence confirms that the abnormal expression of long non-coding RNA (lncRNA) plays an important role in PD. Our previous study found that exogenous α-Syn-induced the downregulation of lncRNA-T199678 in SH-SY5Y cells via a gene microarray analysis. This finding suggested lncRNA-T199678 might have a potential pathological role in the pathogenesis of PD. This study aimed to explore the influence of lncRNA-T199678 on α-Syn-induceddopaminergic neuron injury. Overexpression of lncRNA-T199678 ameliorated the neuron injury induced by α-Syn via regulating oxidative stress, cell cycle, and apoptosis. Studies indicate lncRNAs could regulate post-transcriptional gene expression via regulating the downstream microRNA (miRNA). To discover the downstream molecular target of lncRNA-T199678, the following experiment found out miR-101-3p was a potential target for lncRNA-T199678. Further study showed that the upregulation of lncRNA-T199678 reduced α-Syn-induced neuronal damage through miR-101-3p in SH-SY5Y cells and lncRNA-T199678 was responsible for the α-Syn-induced intracellular oxidative stress, dysfunction of the cell cycle, and apoptosis. All in all, lncRNA-T199678 mitigated the α-Syn-induced dopaminergic neuron injury via targeting miR-101-3p, which contributed to promote PD. Our results highlighted the role of lncRNA-T199678 in mitigating dopaminergic neuron injury in PD and revealed a new molecular target for PD.